The effect of guided-discovery instructional strategy on learner performance in chemical reactions in grade 9 in Mankweng Circuit - Maake, Mampageti Rebecca (My University, 2019)
The purpose of this study was to investigate the effect of guided discovery instructional strategy on the grade 9 learners’ performance in chemical reactions. Secondly, to determine the effect of guided discovery instructional strategy on gender (boy and girl). The quantitative, descriptive and inferential research was conducted to determine if there were any differences between the performance of learners taught using Guided discovery and learners taught using direct instruction. Data collection was done using pre-test and post-test. Two groups of learners participated in the study. The experimental group (n = 40) was taught through Guided discovery. The second was Control Group (n = 35) taught through direct instruction. The findings reveal that guided discovery instructional strategy resulted in better performance of learners in science than direct instruction. Learners expressed an increased interest, motivation and self-efficacy after being exposed to guided discovery. Therefore, the study recommends that teachers need to move learners from dependent direct instruction to more independent learning through guided instruction. KEY TERMS Guided discovery learning, performance, learner
Thesis (M. Ed.) -- University of Limpopo, 2019
Keywords: Guided discovery learning; Performance; Learner; Instructional systems; Academic achievement; Learner autonomy